2-step integral backstepping control of the two-rotor aero-dynamical system (TRAS) - Haruna, Ado (Univ El Oued, Fac Science & Technology, 2017)
This work proposes a simplified nonlinear backstepping control method for fast trajectory tracking of a 2-DOF laboratory helicopter called the Two Rotor Aero-dynamical System (TRAS). The relative degree 3 system is decomposed into the yaw subsystem (YS) and the pitch subsystem (PS) and an integral backstepping controller (IBC) is designed for each subsystem with the coupling effects considered as uncertainties. The control design considers the system as having relative degree 2, resulting in a much less complex 2-step backstepping control law requiring partial state feedback. Real time experiments show good tracking ability of the proposed method to different input waveforms within a wide operating range.